Comparative efficacy and acceptability of selective serotonin reuptake inhibitor antidepressants for binge eating disorder: A network meta-analysis - Duan, Hanying; Zhu, Lijun; Li, Min; Zhang, Xinyue; Zhang, Beilin; Fang, Shaokuan (Frontiers in Pharmacology, 2022)
Background: There are several selective serotonin reuptake inhibitor (SSRI) antidepressants currently used to treat binge eating disorder (BED), but the efficacy and acceptability of these antidepressants are still controversial. Therefore, we designed a network meta-analysis (NMA) to compare the efficacy and acceptability of different SSRI antidepressants for the treatment of BED. Methods: Four databases including PubMed, Embase, the Cochrane Library, and Web of Science were systematically searched for the eligible randomized controlled trials (RCTs) for the treatment of patients with BED. The analysis was performed with Stata16 software. Results: 9 RCTs were included in this NMA. The results of the study showed that compared with placebo, sertraline and fluoxetine could significantly reduce the frequency of binge eating. Fluoxetine was shown to be the drug with the greatest reduction in Hamilton Rating Scale for Depression (HAMD) score. Besides, all SSRI antidepressants were ineffective in losing weight. In addition, all the investigated antidepressants were found to be well acceptable in regards to the acceptability reflected by the dropout rate. Conclusion: As far as both efficacy and acceptability were concerned, fluoxetine might be the best choice.